Japanese Social Interaction in Sento - Ariestafuri, Nurza; Gunawan, Hero; Gayatri Ranadireksa, Dinda (International Journal of Psychosocial Rehabilitation, 2020)
This cultural article discusses sento as a place of Japanese social interaction. Sento is a bath house or public bathing place that is commonly found in Japan where visitors must pay money to be able to use this facility. Although today the number of sentos is not as much as before, this place remains one of the places visited because of social reasons. It is also commonly called the hadaka tsukiai or naked meetings. Sento visitors usually get to know each other, it happens often they meet at the place and interactions also occur between users of Sento services.